Matematyka 3 przyklady A B C



Matematyka 3 Przyklady A B C class=

Odpowiedź :

a) x² - (2-x)² = 8

x² - (2² - 2 · 2 · x + x²) = 8

x² - (4 - 4x + x²) = 8

x² - 4 + 4x - x² = 8

-4 + 4x = 8

4x = 8 + 4

4x = 12   /:4

x = 3

b) (3x + 1)² - 9x² = 7

(3x)² + 2 · 3x · 1 + 1² - 9x² = 7

9x² + 6x + 1 - 9x² = 7

6x + 1 = 7

6x = 7 - 1

6x = 6   /:6

x = 1

c) (x + 1)² - (x + 1)(x - 1) = 12

x² + 2 · x · 1 + 1² - (x² - 1²) = 12

x² + 2x + 1 - x² + 1 = 12

2x + 2 = 12

2x = 12 - 2

2x = 10   /:2

x = 5